Analysis of Factors Affecting Online Purchase Decisions in Manado City, North Sulawesi - Iskandar Rifai (Green Economics: International Journal of Islamic and Economic Education, 2025)
This study aims to determine and analyze the key factors that influence and significantly contribute to online purchasing decisions among consumers in Manado City, North Sulawesi. The research adopts a quantitative approach with factor analysis as the main method of data analysis. Judgmental sampling was employed to select participants who have experience in online shopping. Based on the results, seven dominant factors were identified that affect consumer decisions when making online purchases. These factors include: (a) Consumer Limitations and Access, which refer to time constraints and limited access to physical stores; (b) Desire and Technology, highlighting the role of consumer interest and technological literacy; (c) Product and Price Limitations, involving the lack of product variety and pricing differences; (d) Flexibility, which represents the freedom to shop anytime and anywhere; (e) Efficiency, such as time and cost savings; (f) Convenience, referring to the ease of the purchasing process; and (g) Economy and Social, which include discounts, promotions, and social influences. The study contributes to a better understanding of consumer behavior in digital commerce and provides useful insights for businesses and marketers to improve online customer experiences, particularly in regional markets such as Manado. The findings underscore the multidimensional nature of online shopping behavior in a rapidly growing digital economy.